Qui fabrique et qui regarde ? - Isabelle Singer et Philippe Morice (Mise au Point)
As researchers attached to film aesthetics, as teachers concerned with giving students in the professional Master degree the technical and theoretical tools necessary for their work, and as professionals aware of the balance between artistic projects and the economic reality they are part of, we have tried in this paper to avoid limiting film making to an opposition between theory and fact. In keeping with Marie Jose Mondzain, we hope to reduce the division between the producers and the receivers of images. To achieve this we have relied on the various aspects that are taken into account on film sets: according to Jean-Cesar Chiabaut, a cameraman who worked with Robert Besson in particular:”our attitude is “we put the camera there” (Bardet, 2008, 41); for Jacques Loiseleux, cameraman for Maurice Pialat among others, the question is: “What do we put inside and what do we leave outside?” (Loiseleux, Umanski, Brenez, 2005) Alexander Astruc justifies his great admiration for Howard Hawkes by saying that “a man who is capable of producing films like Rio Bravo and El Dorado and at the same time of making Red River, in other words of solving the practical problem of having 200 cows cross a stream, that person is a genius. For Astruc film making is, “both the idea and the realization of the idea. If there is no idea there is nothing, and if you don’t carry out the idea there is nothing either. It’s a to-and-fro movement between the idea-the transcendence-and the execution or the concrete.”(L’Homme à la camera-stylo, 2008)All these reflections can be summarized in one simple question : where do you place the camera equipped with which optics—understood to be : supporting which idea… ?